Konseling dan Pemeriksaan Kesehatan Mata pada Pengabdian Masyarakat di Kelurahan Paal Lima Kecamatan Kota Baru Kota Jambi: Pengabdian - Rica Tri Septinora; Sri Mulyati; Chrismis Novalinda Ginting; Dwight Mahaputera Marulitua Hutapea; I Nyoman Ehrich Lister (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Eye health is often overlooked, leading to many eye diseases that, if not properly treated, can cause visual impairment. Visual impairment remains a significant health issue both globally and in Indonesia, as it can interfere with a person’s daily activities. A tangible impact of impaired visual acuity is a decline in academic performance due to difficulty seeing writing from a distance, ultimately preventing children from fully absorbing the lessons taught. This community service activity aims to increase public knowledge and awareness of eye health through health education and direct eye examinations in Kota Baru Sub-district, Jambi City. The methods used include eye examinations, counseling, and distribution of takjil. The results of this service showed strong public enthusiasm and an improvement in understanding the importance of maintaining eye health. This activity is expected to have a long-term impact on healthy lifestyle behaviors related to vision.